Low voltage blue-phase liquid crystal display with insulating protrusion sandwiched between dual-layer electrodes. Issue 4 (16th March 2019) - Guo, Yuqiang; Wang, Yifei; Zhang, Chi; Mu, Qihui; Li, Xiaoshuai; Dou, Hu; Chu, Fan; Ma, Hongmei; Zhang, Hui; Sun, Yubao; Wang, Qionghua
ABSTRACT: In order to lower the operating voltage of blue-phase liquid crystal display (BPLCD), a BPLCD with insulating protrusion, which is sandwiched between dual-layer electrodes, is proposed. There are four electrodes in this structure; thus, we investigate different driving methods to find a proper driving method. The effect of protrusion's dielectric constant on operating voltage of the proposed BPLCD is explored under various electrodes' parameters. As a result, the operating voltage of the proposed BPLCD with protrusion's dielectric constant of 1, 000 is 9.8 V, which is reduced by 4.67× compared with that of conventional in-plane switching (IPS) BPLCD (45.8 V). Moreover, the zigzag electrode structure is adopted to reduce the large off-axis image distortion index. Besides, the azimuth distortion index is defined to describe the gamma shift between the minimum and maximum gamma shift curves at a certain polar angle. The results show that the off-axis image distortion index can be reduced to 0.0834, the azimuth distortion index is 0.0810 and the viewing cone of contrast ratio larger than 1, 000:1 is over 50ºas the zigzag proposed BPLCD is used. Graphical Abstract: